Supernovae and Single-Year Anomalies in the Atmospheric Radiocarbon Record. Issue 2 (1st August 2016) - Dee, Michael; Pope, Benjamin; Miles, Daniel; Manning, Sturt; Miyake, Fusa
Abstract: Single-year spikes in radiocarbon production are caused by intense bursts of radiation from space. Supernovae emit both high-energy particle and electromagnetic radiation, but it is the latter that is most likely to strike the atmosphere all at once and cause a surge in 14 C production. In the 1990s, it was claimed that the supernova in 1006 CE produced exactly this effect. With the 14 C spikes in the years 775 and 994 CE now attributed to extreme solar events, attention has returned to the question of whether historical supernovae are indeed detectable using annual 14 C measurements. Here, we combine new and existing measurements over six documented and putative supernovae, and conclude that no such astrophysical event has yet left a distinct imprint on the past atmospheric 14 C record.